2008
DOI: 10.1111/j.1742-4658.2008.06472.x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the glutamine synthetase/glutamate synthase pathway in conditioning the amino acid metabolism in bundle sheath and mesophyll cells of maize leaves

Abstract: In the C 4 plant maize, inorganic nitrate reduction to ammonium and subsequent ammonium assimilation into amino acids occur in two different photosynthetic cells: bundle sheath cells (BSCs) and mesophyll cells (MCs). Nitrate taken up by roots moves in part, via the vascular bundle, to leaves for reduction. We investigated the role of glutamine synthetases (cytosolic GS1 and chloroplast GS2) and glutamate synthases (ferredoxin-GOGAT and NADH-GOGAT) in the inorganic nitrogen assimilation and reassimilation into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…However there are very few reports on the diurnal regulation of GS expression, and most of them have been devoted to roots [28-32]. Our results reveal that the circadian clock influences the expression of GS genes in M. truncatula at the transcriptional, translational and post-translational levels.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However there are very few reports on the diurnal regulation of GS expression, and most of them have been devoted to roots [28-32]. Our results reveal that the circadian clock influences the expression of GS genes in M. truncatula at the transcriptional, translational and post-translational levels.…”
Section: Discussionmentioning
confidence: 56%
“…MtGS2a mRNA accumulates during the start of the light period and this is accompanied by a slight increase in polypeptide abundance, however total GS activity in the leaves decreases within the first 30 minutes of light. Similarly, it was reported that ZmGln2 mRNA peaks early in the light period in maize leaves [32]. The main function of the plastid-located GS in leaves of C 3 plants is the assimilation of ammonium resulting from photorespiration [13].…”
Section: Discussionmentioning
confidence: 97%
“…As shown in Figure 6C, the linear incorporation of 14 C into polar metabolites including 2-OG was similar or slightly less in dct2-1 relative to the wild type and suggested that nitrogen exchange in BS cells was not significantly compromised by the mutation. Although the malate availability for counter-port activity could be compromised in dct2-1 plants, alternative reactions catalyzed by glutamine or asparagine synthetase, glutamate synthase, and glutamate dehydrogenase outside of the chloroplast could also be involved in ammonia recycling (Becker et al, 2000;Miflin and Habash, 2002;Valadier et al, 2008). Transcriptionally upregulated asparagine synthetase (Supplemental Data Set 1) and the accumulation of asparagine (Supplemental Table 1) were observed in dct2-1.…”
Section: Conversion Of Glutamate To 2-oxoglutarate Is Unaffected By Dmentioning
confidence: 99%
“…Inasmuch as arginine synthesis from CP relies on the regulation of glutamate conversion to ornithine [6], we studied the impact of CPSase on overall arginine synthesis in the carB mutant. In fact, amino acid synthesis is tightly correlated with amino acid transport under the fine control of the cellular and subcellular expression of the nitrogen assimilatory genes and of the encoded enzymes [12]. Despite their primary importance, the spatial location and expression patterns have not been investigated for Fd‐GOGAT isoenzymes, NADH‐GOGAT and CPSase in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%